UJI AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH JERUK NIPIS (Citrus aurantifolia Swingle) TERHADAP PERTUMBUHAN BAKTERI ISOLAT KLINIS - Rohmi Wardani; Dwi Soelistya Dyah Jekti; Prapti Sedijani (Jurnal Penelitian Pendidikan IPA, 2019)
The objective of this research was to test antibacterial activity ethanol and ethyl acetate of lime peel (Citrus aurantifolia Swingle) extract by Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) against the growth of clinical isolate bacteria. The type of this study used laboratory experimental using sensitivity test, dilution of tube and spreading plate. The experimental design used Complete Random Design using three repetitions on three concentrations i.g 25, 50, and 75%. Data was analyzed by qualitative with measuring inhibit diameter zone bacterial and qualitative using Two Way Anova followed by BNT with α= 5%. The statistical analysis showed that the solvent factor and concentration factor was significantly against growing bacterial and there was an interaction affect of both factors on S. aureus growth. The result presented that the ethanol and ethyl acetate of lime peel extract strongly inhibited Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa; and midly inhibited the growth of Klebsiella pneumoniae. The MIC ethanol and ethyl acetate of lime peel extract against S. aureus, S. epidermidis and P. aeruginosa was 25% and K. pneumoniae was 50%. The MBC showed that ethanol and ethyl acetate of lime peel  extract killed bacteria P. aeruginosa at 15%, S. aureus, S. epidermidis at 20% and K. pneumoniae at 25%. Taken together, it can be concluded that ethyl acetate of lime extract more effective than that of ethanol extract was to inhibit and killed clinical isolate bacterial.Keywords: lime peel (Citrus aurantifolia Swingle), antibacterial activity, clinical isolate bacteria, MIC and MBC.